DAMPAK PANDEMI COVID-19 TERHADAP PELAKSANAAN PEMBELAJARAN ANAK USIA DINI : (Studi Kasus di PAUD Raudatussibyan Al-Mannan Dusun Bagik manis Desa Kembang Kerang Daya Kecamatan Aikmel Lombok Timur) - Nurhasanah, Nurhasanah; Husnaini, Nani; Indira Astriya, Baiq Roni (Jurnal al Muta'aliyah: Pendidikan Guru Madrasah Ibtidaiyah, 2022)
Abstract The purpose of this study is to obtain information related to the impact of the Covid-19 pandemic on the implementation of early childhood learning and the form of synergy that teachers make in providing education to children during the Covid-19 pandemic. This research uses qualitative research methods with a case study approach, techniques, data used, namely, observation, interviews, and documentation. The data analysis technique used is the Mulles and Huberman analysis technique which consists of data reduction, data presentation, and drawing conclusions (levers). The results of this study are as follows: there are several impacts of the Covid-19 pandemic that are most dominant seen in Raudatussibyan Al-Mannan Dusun Bagik Manis on the implementation of early childhood learning including the impact on learning activities at school, the impact on learning activities at home, and impact on changes in children's attitudes and behavior. Meanwhile, the synergy carried out by teachers and parents at Paud Raudatussibyan Al-Mannan Bagik Manis Hamlet in providing education during the Covid-19 pandemic includes synergy in the children's learning process, synergy in the process of evaluating forms of learning.